Studies of Short Range Correlations in inverse kinematics at BM@N at the NICA facility. (November 2019) - Galavanov, A; Khabarov, S; Kirushin, Y; Kulish, E; Lenivenko, V; Makankin, A; Maksymchuk, A; Palichik, V; Patsyuk, M; Vasiliev, S; Zamiatin, N
Abstract: NICA-Nuclotron (Nuclotron-based Ion Collider fAility) is a new accelerator complex being constructed at the Joint Institute for Nuclear Research (Dubna, Russia) to study properties of dense baryonic matter. BM@N (Baryonic Matter at Nuclotron) is the first fixed target experiment at the NICA-Nuclotron facility. The aim of the experiment is to study collisions of relativistic ion beams of the kinetic energy from 1 to 4.5 AGeV with fixed targets. BM@N energies are perfectly suitable for strange hypernuclei investigation. This year BM@N started a new physics program aiming at studying the Short Range Correlations (SRC). SRC are brief fluctuations of two nucleons with high and opposite momenta, where each of them is higher than the Fermi momentum for the given nucleus, and the center of mass momentum is close to zero. The presence of SRC pairs within nuclei and their properties have important implications for nuclear physics, high energy physics, and astrophysics. The BM@N setup uses a carbon beam hitting a liquid hydrogen target, which makes it possible to detect the residual nucleus after hard knock-out of the two SRC nucleons. We present an overview of the main detection systems used for the SRC measurement as well as the first results from the tracking detectors.